Customs Union from a Single-Country Viewpoint - Gehrels, Franz (Review of Economic Studies, 1956)
Journal Article Customs Union from a Single-Country Viewpoint Get access Franz Gehrels Franz Gehrels Bloomington, Indiana Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 61–64, https://doi.org/10.2307/2296237 Published: 01 July 1956